UNEARTHING STUDENTS’ REALIZATION OF SPEECH ACT IN ASKING INFORMATION IN TELEPHONE CONVERSATION - Ida Zuraida Supri (University of Kuningan, 2017)
This research aims at investigating speech acts realization in asking for information in Bahasa Indonesia done by students at Widyatama University. Secondly, it seeks for the utterance patterns highly used by students in asking for information using Bahasa Indonesia. The study utilized a descriptive method. This method comprises distributing questionnaires, collecting data, classifying data, and analyzing data. The subjects in this study were fourth semester students of Information Technology, Faculty of Engineering. The results showed that speech realization patterns highly used when they ask for information via telephone to a friend is they make an opening and directly to the purpose of calling, and closing. When calling to parents, casual utterances are significantly employed.Keywords: speech acts, utterance patterns